Political economy of «velvet revolution»: features and lessons - Manaseryan, Tatul N. (Journal of the Belarusian State University. Sociology, 2019)
The article discusses the economic aspects of the «velvet revolution» in Armenia. Based on an analysis of the main trends in the economy, society and politics, an attempt is made to identify the main features of the revolution, emphasizing its local, regional and possible international importance. Attention is paid to the social and economic causes of the revolution, as well as national peculiarities of the implementation of the idea of changing power exclusively by peaceful means. Based on the way the new authorities declare, the main achievements in the field of economics and social security after the political events in April – May 2018 are presented. Also, the main omissions that take place in the country, in particular, in the area of personnel policy, factors negatively influencing the formation of a favorable investment environment and other obstacles to development are emphasized. Taking into account the peculiarities, achievements and omissions, the lessons of the «velvet revolution» are presented for both Armenia and other countries.
Keywords: «velvet revolution»; economic transformations; personnel policy; tax system; accumulative pension system; revolution lessons